Railway station evaluation for systematic train forming on the railway network - Čamaj, Juraj; Gašparík, Jozef (Univerzita Pardubice, 2008)
Paper submitted the evaluation of the railway stations by the multi criterions evaluation. The resulting indicator is characterized station as weight point in the valuation graph. The evaluation of stations is a very important element in determining investment in technical equipment stations using technology for time-discrete train formation on railway network.
Hodnotenie železničných staníc pre systematickú vlaotvorbu na železničnej sieti
Bewertung der Eisenbahnstation für den systematischen Wagensatz auf dem Eisenbahnnetz